2020
DOI: 10.5829/ijee.2020.11.03.05
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Earth’s Solar Irradiance Across Some Selected Stations in Sub-Sahara Region of Africa

Abstract: Solar radiation is an important parameter in the study of electricity and/or thermal system installation. Direct monthly irradiance data measurements of the earth's horizontal surface irradiance for the year 1985 to 2019 for nine stations (Sokoto,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In commaseparated value (CSV) data format, data for thirty-four (34) years covering 1985 to 2019 were retrieved as monthly averages for January to December of each year. The data was collected using the method described in literature [25][26][27][28]. Environmental running of statistical packages (i.e The Mann-Kendal statistics was used to analyze the trend in rainfall series while the normality of rainfall series was determined using the Kolmogorov-Smirnov test) was done for data plotting and curve fittings.…”
Section: Methodsmentioning
confidence: 99%
“…In commaseparated value (CSV) data format, data for thirty-four (34) years covering 1985 to 2019 were retrieved as monthly averages for January to December of each year. The data was collected using the method described in literature [25][26][27][28]. Environmental running of statistical packages (i.e The Mann-Kendal statistics was used to analyze the trend in rainfall series while the normality of rainfall series was determined using the Kolmogorov-Smirnov test) was done for data plotting and curve fittings.…”
Section: Methodsmentioning
confidence: 99%
“…The data used in this study consist of monthly rainfall, air temperature, relative humidity, atmospheric pressure, wind speed and direction for five stations obtained from the archive of the HelioClim website of Soda (http://www.soda-pro.com) of MERRA-2 meteorological Re-Analysis data (Gelaro et al 2017, Aweda et al 2020a, Aweda et al 2020b, Aweda et al 2021a, Adebayo et al 2022. The data of forty-one years spanning from 1980 to 2020 were obtained as a monthly average from January to December of every year in Comma Separated Value (CSV) data format.…”
Section: Data Collection and Preparationmentioning
confidence: 99%
“…The estimated and measured results were compared using statistical parameter tests such as the mean bias error (MBE), mean percentage error (MPE), mean absolute error (MAE), RMSE, and coefficient of determination (R²). In some work the researchers [20] used ARIMA models to simulate solar irradiance in nine Nigerian locations. Findings revealed that in Kebbi, Iwo, and Maiduguri, the best forecasting ARIMA was (3,0,3), in Calabar as well as Sokoto, it was ARIMA (2,0,2), and in other study areas like Enugu, Ikeja, Ilorin, and Port Harcourt, ARIMA (2,0,3) was the better model for forecasting irradiance.…”
mentioning
confidence: 99%